Pengaruh Kepemimpinan, Pemberdayaan, dan Stres Kerja Terhadap Komitmen Organisasional serta dampaknya terhadap Kinerja Dosen - Idayanti Nursyamsi (Conference In Business, Accounting, And Management (CBAM), 2012)
This research aimed to examine the effects of leaderships, empowerments and working pressures towards organizational commitment as well as its impact on lecturers’ performance. This is a descriptive research with populations of 143 lecturers of Economics and Business Faculty, Hasanuddin University. Selected samples were 100 lecturers obtained through cluster sampling, stratified sampling and proportionate random sampling techniques. Method of analysis used in this research was path analysis processed with SPSS program version 20.0. The result of research shows that there are directly positive and significant effects between leaderships and mpowerments towards organizational commitment and lecturers’ performances, while variable of working pressures has directly negative and significant effects towards organizational commitment and lecturer’s performance. Variable of empowerment has the most dominant contribution and directly affecting, even if it is seen by indirect effects.Keywords : leaderships, empowerments, working pressures, organizational commitment, lecturers’ performance